The Use of Conjunctions in Buginese Compound Sentences in Junior High School Students - Wahyuni Wahyuni; Syamsudduha Syamsudduha; Sultan Sultan (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. This study aims to describe the use of conjunctions in buginese compound sentences of eighth grade students of the Soppeng State Junior High School. And describe errors in compound sentences of eighth grade students of State Junior High School one Soppeng in Bugis language. This research is a qualitative research. The data in this study are conjunctions in Bugis compound sentences obtained from eighth grade students of the Soppeng State Junior High School. Data collection techniques in this study were carried out by tests. The data analysis technique was carried out in three stages, namely, (1) classifying all conjunctions based on their types, (2) analyzing the use of conjunctions, (3) drawing conclusions from the results of the analysis. On the accuracy of use and forms of errors in the use of conjunctions in equivalent compound sentences include (1) compound sentences equivalent to addition, (2) compound sentences equivalent to resistance, (3) compound sentences equivalent to choice. (1) compound sentences with subject density, (2) compound sentences with object density, (3) compound sentences with predicate density, (4) compound sentences with adverb density. Furthermore, (5) the accuracy of the use and forms of errors in the use of conjunctions in mixed compound sentences. After finding the accuracy of the use and the form of errors in the use of conjunctions in Bugis compound sentences, the researcher can conclude that students' understanding of the use of conjunctions in compound sentences is still low or not capable. Keywords: conjunctions, compound sentences.